Microbiological indicators of tropical soils quality in ecosystems of the north-east area of Peru - Valdez-Nuñez, Renzo (2019)
Tropical soils withstand heavy pressure due to deforestation as a result of the change in land use, decreasing their quality. Traditionally, the quality of soil has been based on physical and chemical indicators; however, the biological ones can predict variations in the quality, in an early and effective way. In this research, the microbiological quality of soils from two ecosystems was evaluated, one from the Cumbaza Sub-Basin (CSB) and the other from Degraded Pastures at Cuñumbuque (DPC), both in San Martín, Peru. The physicochemical characteristics were studied and the microbial populations of Total Bacteria (TB), Sporulated Bacteria (SB), Total Fungi (TF), Actinobacteria (ACT), and parameters of microbial activity such as Basal Respiration (BR), Microbial Biomass (MB), Metabolic Quotient (qCO2) and Microbial Quotient (qMIC). According to the Principal Component Analysis (PCA), the soils of the CSB had on average a lower biological quality compared to the DPC soils. The PCA discriminated that the microbial populations of TB, SB, ACT and MB represented effective microbiological indicators to evaluate the quality of the soils, in this respect the soils of Shapumba, Chontal, Aucaloma and Vista Alegre are degraded and require the application of new technologies and public policies for their recovery.